2020
DOI: 10.3390/microorganisms8122027
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Metals and Metalloids by Actinobacteria: Cell Resistance Mechanisms and Synthesis of Metal(loid)-Based Nanostructures

Abstract: Metal(loid)s have a dual biological role as micronutrients and stress agents. A few geochemical and natural processes can cause their release in the environment, although most metal-contaminated sites derive from anthropogenic activities. Actinobacteria include high GC bacteria that inhabit a wide range of terrestrial and aquatic ecological niches, where they play essential roles in recycling or transforming organic and inorganic substances. The metal(loid) tolerance and/or resistance of several members of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 259 publications
(212 reference statements)
0
16
0
Order By: Relevance
“…In this line, bacteria-producing metal nanomaterials with antimicrobial properties are a realistic biotechnological promise toward sustainability [5]. Bacteria reduce metal ions, chalcogens oxyanions, or other elements using NADH-or NADPH-dependent reductases, catalases, and terminal oxidases or by non-enzymatic routes such as thiol groups, and phosphates, among others [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In this line, bacteria-producing metal nanomaterials with antimicrobial properties are a realistic biotechnological promise toward sustainability [5]. Bacteria reduce metal ions, chalcogens oxyanions, or other elements using NADH-or NADPH-dependent reductases, catalases, and terminal oxidases or by non-enzymatic routes such as thiol groups, and phosphates, among others [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Rhodococcus spp. are able to bioconvert toxic metal(loid)s generating nanostructures with biomedical, electronic, and environmental applications ( Presentato et al, 2018b , c , 2019 , 2020 ). For instance, R .…”
Section: Production Of Valuable Natural Productsmentioning
confidence: 99%
“…Despite their ability to lower their intracellular pH and salinity, haloalkaliphilic species must still be able to secrete stable and operational enzymes at elevated pH and salinity (Mamo, 2020), making BRDAs potential sources of these enzymes. Some of the haloalkaliphilic bacteria known to synthesize alkaline-active enzymes, namely Gammaproteobacteria, Actinobacteria and Firmicutes (Kalwasińska et al, 2018;Litchfield, 2011;Maharaja et al, 2018;Shameer, 2016;Shivlata and Tulasi, 2015), are also capable to modify the chemical phase and mobility of various critical metals (Chidambaram et al, 2010;Presentato et al, 2020;Wee et al, 2014), including REEs. For example, Maleke et al (2019) reported the direct reduction of Eu 3+ to Eu 2+ by Clostridium sp.…”
Section: Implications For Bioremediation and Metal Recoverymentioning
confidence: 99%